2021
DOI: 10.1097/fbp.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of nicotine reinforcement and cue reactivity: a translational study in humans and rats

Abstract: Relapse is common amongst smokers attempting to quit and tobacco cue-induced craving is an important relapse mechanism. Preclinical studies commonly use cue-induced reinstatement of nicotine seeking to investigate relapse neurobiology. Previous research suggests dependence severity and nicotine intake history affect smoking resumption and cue-induced reinstatement of nicotine seeking. However, behavioural data may be interpreted in terms of nicotine reinforcement. This translational study investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Network activity correlated close to significance ( p = 0.0545) with relapse-like behavior after 28 d of nicotine abstinence which was associated with total nicotine exposure. This suggest that activity of the DLS-amygdala network is related to nicotine seeking which in turn is affected by nicotine exposure ( X. Liu et al, 2008 ; Butler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Network activity correlated close to significance ( p = 0.0545) with relapse-like behavior after 28 d of nicotine abstinence which was associated with total nicotine exposure. This suggest that activity of the DLS-amygdala network is related to nicotine seeking which in turn is affected by nicotine exposure ( X. Liu et al, 2008 ; Butler et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…56 A large volume of human and non-human animal studies have shown that organisms will exert high levels of effort to obtain especially potent reinforcers, such as high-fat foods, nicotine, and other drugs. [57][58][59][60][61] Further, the degree to which individuals will exert effort towards certain problematic behaviors has been associated with negative psychological and health outcomes (e.g., effort for nicotine is higher in heavy smokers, effort for food is higher for binge eating). 62,63 These findings correspond with the clinical phenomenon that some individuals will go to great lengths to engage in addictive behaviors because of the strong reward derived from those behaviors.…”
Section: Comparing Learned Industriousness To Other Theories Of Effor...mentioning
confidence: 99%
“…It is well-known that drug-associated cues play a large role in the formation and continuation of drug taking behaviors, and the presence of drug-paired cues is of particular importance in nicotine self-administration behavior (Butler, Forget, Heishman et al, 2021; Caggiula, Donny, Palmatier et al, 2009; Caggiula, Donny, White et al, 2001; Chaudhri, Caggiula, Donny et al, 2007; Donny, Caggiula, Knopf et al, 1995; Donny, Chaudhri, Caggiula et al, 2003; LeSage, Burroughs, Dufek et al, 2004; X. Liu, Caggiula, Yee et al, 2006; Sorge, Pierre, & Clarke, 2009).…”
Section: Introductionmentioning
confidence: 99%